Pengembangan Buku Ajar Fisika Solar Cell Berbasis Pedagoical Content Knowledge - Boisandi, Boisandi (Kappa Journal, 2023)
Physics solar cell  is a subject in the physics education at the IKIP PGRI Pontianak. Learning outcomes and graduates in the curriculum include being able to analyze subject matter (pedagogical content knowledge). The observations of researchers while giving solar cell physics lectures show that students pay less attention to the importance of understanding the relationship between learning outcomes and teaching materials during lectures. Thus this phenomenon was appointed as one of the lecture evaluations. The results of the evaluation of the lectures obtained recommendations for the development of textbooks so that they are adapted to learning outcomes and graduates referring to the physics education curriculum at the IKIP PGRI Pontianak. Based on these things, the researcher is trying to develop a textbook based on PCK (pedagogical content knowledge) which contains material content and analysis content according to learning outcomes and graduates in the curriculum of the Physics Education IKIP PGRI Pontianak. This study aims to determine the feasibility of PCK-based physics solar cell  textbooks according to experts. The research method uses research and development design with the stages of information gathering and reference, design, development, product, validation, revision, product. The research was carried out in Physics Education, IKIP PGRI Pontianak. Data collection techniques in the form of indirect communication techniques. Overall, PCK-based physics solar cell  textbooks have been produced. The results of the validation show that textbooks have an average validation score of 77.77% with the Eligible.